Administrative act, nullity of full nullity and crime: An analysis of art. 10.4 of the LPAG - Picón Arranz, Alberto (Revista de Derecho, 2024)
After a brief exposition of the status quaestionis of the theory of the invalidity of administrative acts in the LPAG, the main objective of this paper is to carry out a detailed study of the cause of full nullity concerning administrative acts constituting a crime or dictated as a consequence of it, set out in art. 10.4 LPAG. On the one hand, it studies the material requirements that must be met by the act and, on the other hand, it examines the role that criminal jurisdiction can play, as well as its limits, when declaring the full nullity of the administrative act on this ground.